Giving Counsel: Donald Capps' Contributions to Pastoral Counseling - LaMothe, Ryan (Journal of religion and health, 2018)
This article explores some of Donald Capps' contributions to the ministry of pastoral counseling. In particular, several key attributes of pastoral counseling as a ministry of the church are identified and discussed. This is followed by identifying six features necessary for good enough pastoral counseling. A final brief section offers some musings that I wish Capps could respond to.